Comparison of SOX2 and POU5F1 Gene Expression in Leukapheresis-Derived CD34+ Cells before and during Cell Culture - Świstowska, Małgorzata; Gil-Kulik, Paulina; Czop, Marcin; Wieczorek, Katarzyna; Macheta, Arkadiusz; Petniak, Alicja; Cioch, Maria; Hus, Marek; Szuta, Mariusz; Rahnama-Hezavah, Mansur; Płachno, Bartosz J.; Kocki, Janusz (International journal of molecular sciences, 2023)
Bone marrow is an abundant source of both hematopoietic as well as non-hematopoietic stem cells. Embryonic, fetal and stem cells located in tissues (adipose tissue, skin, myocardium and dental pulp) express core transcription factors, including the SOX2, POU5F1 and NANOG gene responsible for regeneration, proliferation and differentiation into daughter cells. The aim of the study was to examine the expression of SOX2 and POU5F1 genes in CD34-positive peripheral blood stem cells (CD34+ PBSCs) and to analyze the influence of cell culture on the expression of SOX2 and POU5F1 genes. The study material consisted of bone marrow-derived stem cells isolated by using leukapheresis from 40 hematooncology patients. Cells obtained in this process were subject to cytometric analysis to determine the content of CD34+ cells. CD34-positive cell separation was conducted using MACS separation. Cell cultures were set, and RNA was isolated. Real-time PCR was conducted in order to evaluate the expression of SOX2 and POU5F1 genes and the obtained data were subject to statistical analysis. We identified the expression of SOX2 and POU5F1 genes in the examined cells and demonstrated a statistically significant (p < 0.05) change in their expression in cell cultures. Short-term cell cultures (<6 days) were associated with an increase in the expression of SOX2 and POU5F1 genes. Thus, short-term cultivation of transplanted stem cells could be used to induce pluripotency, leading to better therapeutic effects.